PERAN FILSAFAT OLAHRAGA DALAM MEMBENTUK IDENTITAS PROFESIONAL PELATIH OLAHRAGA - Chrystian Rambe; Ahmad Avandi; Basyaruddin Daulay; Ghozi Indra Waskita (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2026)
This study aims to analyze the role of sports philosophy in shaping the professional identity of sports coaches through the integration of ontological, epistemological, and axiological dimensions. The background of the study is based on the tendency of coaching practices to emphasize technical and managerial aspects, while the philosophical foundation has not been studied comprehensively. The study uses a literature review approach with an analytical-conceptual design through the stages of identification, selection, evaluation, and synthesis of relevant scientific sources. The results of the study indicate that the ontological dimension shapes coaches' awareness of the nature of sport as a process of developing a whole person; the epistemological dimension emphasizes the importance of integrating scientific knowledge and critical reflection in coaching practice; while the axiological dimension emphasizes the internalization of ethical values, sportsmanship, and moral responsibility. The discussion emphasizes that the professionalism of coaches is not only determined by technical competence, but also by the consistency of values ??and philosophical reflection that underlie their practice. This study concludes that sports philosophy plays a fundamental role in building a professional identity of coaches oriented towards character, integrity, and social responsibility.